Efektivitas Pendidikan Kesehatan Video Animasi tentang Pernikahan Dini terhadap Pengetahuan Remaja Putri - Hanifa Andisetyana Putri; Shusmitha Sekar Satriani; Runjati (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
ABSTRACT Background: The phenomenon of early marriage during the COVID-19 pandemic that occurred in Batang Regency increased by 200% compared to the previous year with the average age of marriage being 17 years. From 2019 to 2020 there has been a decrease of 0.6%, but it has not yet reached the target of reducing it to 8.74% in 2024. One of the factors causing early marriage is the lack of knowledge of reproductivehealth in adolescents and the risks that can occur due to contraceptives. reproductive organs that are not ready for pregnancy and childbirth. This can increase maternal and infant mortality as a standard for a country's health status. Social and economic impacts also occur due to reduced peer interaction, discontinued education levels, resulting in narrower job opportunities. Purpose: The aim of this study was to determine the effectiveness of health education through animated video media on young women's knowledge of early marriage during a pandemic at SMA Negeri 1 Batang. This type of research uses a quasi-experimental and pretest-posttest with control design. The sampling technique was simple random sampling with a total of 134 respondents. Data collection used a questionnaire filled out online via the Google form. Result: The results of the study showed an increase in the average knowledge score in both the control and experimental groups. In the control group, the increase in score reached 12.69 ± 2.211, while in the treatment group it experienced a higher increase, namely 22.55 ± 7.509. The results of the Mann Whitney test showed that providing health education using animated video media was effective in increasing the knowledge of SMA Negeri 1 Batang students with a p value = 0.000. Keywords: early marriage, animation videos, knowledge